Edukasi Perkembangan Batita Melalui Simulasi Penggunaan Pedoman Stimulasi Dini Di Wilayah Kerja Puskesmas Ranomeeto - Nurdin, Nurdin; Amandaty, Srikandi Puspa; nurjannah, nurjannah; Taamu, Taamu (Poltekkes Kemenkes Kendari, 2023)
The important period in child development is the age under five years. Because during this period, basic growth will influence and determine the child's future. The development stage of toddlers has a critical period, where appropriate stimulation/stimulus is needed so that the potential in children develops optimally, so that during this development period, attention is needed, especially from parents. Objective: to improve education (knowledge) for cadres related to SDIDTK which is needed to improve the quantity and quality of services at the integrated health post. Method: This activity is a community service carried out with a descriptive approach through counseling and simulation. Community service was carried out in the Ranomeeto Health Center hall, South Konawe Regency with a duration of 90 minutes for 1 day with a sample of 30 integrated health post cadres spread across 12 villages/sub-districts in the Ranomeeto Health Center working area. Results: counseling and simulations that have been given with the results of all integrated health post cadres understand very well how to detect toddler growth and development. In general, it provides an overview to cadres of what toddler growth and development are like according to their age and how to stimulate growth and development. Conclusion: The use of KPSP can be used by cadres to detect toddler delays in the Ranomeeto District environment so that they can be stimulated immediately.